Diagnostic efficacy of PET-CT, CT, and MRI in preoperative assessment of mandibular invasion caused by head and neck cancer: A systematic review and meta-analysis. (May 2021) - Cao, Chang; Gan, Xinyan; He, Yan; Su, Yonglin; Liu, Zheran; Hu, Xiaolin; Peng, Xingchen
Highlights: Suspicion of mandibular invasion impacts the treatment, especially mandibulectomy. The diagnostic efficacy of PET-CT, MRI, and CT remains uncertain. Compared with CT, MRI is significantly superior for higher sensitivity. PET-CT, CT and MRI were found to have approximately equal summary diagnostic power. Abstract: Objective: This study aims to conduct a systematic review and meta-analysis of the performance of PET-CT, CT, and MRI in diagnosing mandible invasion induced by head and neck cancer (HNC). Materials and methods: The MEDLINE, Embase, Science Direct, CNKI and CQVIP databases were searched from inception until August 1, 2020. Then, a meta-analysis was conducted to calculate the combined diagnostic values with the corresponding 95% CIs. Two independent researchers completed the full text screening, data abstraction, and risk assessment. Results: This meta-analysis included 53 studies (N = 2 946 participants). For the pooled sensitivity (SEN), MRI (SEN: 0.88, 95% CI: 0.81–0.93) was found to have a significantly higher SEN ( P  = 0.0045), when compared to CT (SEN: 0.77, 95% CI: 0.71–0.82), while compared with PET-CT (SEN: 0.88, 95% CI: 0.64–0.97), the SEN was approximately equal ( P >  0.05). The analysis revealed that the combined specificity (SPE) of MRI (SPE: 0.83, 95% CI: 0.74–0.89) and PET-CT (SPE: 0.81, 95% CI: 0.57–0.93) was lower than that of CT (SPE: 0.87, 95% CI: 0.83–0.90), but there was no statistical significance among these ( P  > 0.05). The comparison of the area under curve (AUC) reflected that PET-CT, CT and MRI have approximately equal summary diagnostic power in detecting mandibular invasion ( P  > 0.05). Conclusion: The findings suggest that compared with CT, MRI is significantly superior for higher SEN in diagnosing mandibular invasion. The SEN of MRI and PET-CT were approximately equal. For the summary of diagnostic power, more prospective clinical trials that directly compare these three methods are needed in the future.